Purpose of Creation and Man’s Moral & Spiritual Responsibilities - Muhammad Zeshan Khan; Dr. Jawaad Haseeb (Journal of Religion and Society, 2025)
This article explores the concept of the purpose of human creation and its moral and spiritual implications from an Islamic perspective. It highlights the Quranic view that mankind was created to worship Allah and fulfill ethical responsibilities on earth. The discussion integrates insights from classical scholars such as Ibn Khaldun and Ibn Kathir, emphasizing that human life is a balance between material needs and spiritual growth. The article further elaborates on the role of prayer, moral conduct, and spiritual purification in shaping an individual’s character and preparing him for eternal success in the Hereafter. The significance of family and communal harmony is also discussed, culminating with the Qur’anic supplication from Surah Ghafir (40:8) which prays for Paradise for the believers and their righteous families. Keywords: Purpose of Creation, Moral Responsibilities, Spiritual Growth, Quranic Perspective, Worship, Ethical Values, Hereafter